Peranan Gerakan Pemuda Ansor Kecamatan Menganti dalam Meningkatkan Pembinaan Al-akhlaqul Karimah - Abdul Mu'id (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2019)
Youth is the spearhead of the nation's future, if the youth has the potential, then the country must become a developed country. As said by Imam Syafii, RA.